Unconventional secretion mediated by direct protein self-translocation across the plasma membranes of mammalian cells - Sparn, Carola; Meyer, Annalena; Saleppico, Roberto; Nickel, Walter (Trends in biochemical sciences, 2022)
In recent years, a surprisingly complex picture emerged about endoplasmic reticulum (ER)/Golgi-independent secretory pathways, and several routes have been discovered that differ with regard to their molecular mechanisms and machineries. Fibroblast growth factor 2 (FGF2) is secreted by a pathway of unconventional protein secretion (UPS) that is based on direct self-translocation across the plasma membrane. Building on previous research, a component of this process has been identified to be glypican-1 (GPC1), a GPI-anchored heparan sulfate proteoglycan located on cell surfaces. These findings not only shed light on the molecular mechanism underlying this process but also reveal an intimate relationship between FGF2 and GPC1 that might be of critical relevance for the prominent roles they both have in tumor progression and metastasis.